Transnational Human Rights Networks During the First Phase of the Chilean Dictatorship (1973-1976): Formation and Strategies (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article analyzes the main characteristics of the transnational human rights networks and the local bodies associated with them that were developed among some of the Christian churches in Chile and international organizations related to the Western ecumenical field during the first phase of the dictatorial government’s repressive plan. Networks, considered as a transnational strategy, are analyzed from the testimony of actors who were part of their management and development. From the political science supposition that affirms that the social practices shape the institutions, it establishes that the formation of local bodies for the protection of human rights was determined by the implementation of a new type of transnational activism in network that transformed the ideological interpretation of the organization and the political struggle, relegating the political aspect for the benefit of language and moral conception, materializing a collective transversal action for human rights.
Keywords: Transnational networks; Ecumenism; Human Rights; Testimony